Logistics Management in Indonesia’s Free Nutritious Meals Program: A Qualitative Case Study of Last-Mile Distribution Challenges - Djamarel Hermanto; Lisnatiawati Saragih (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The Free Nutritious Meals (Makan Bergizi Gratis/MBG) program is one of Indonesia’s most ambitious social logistics undertakings, requiring government agencies to deliver perishable meals daily to millions of beneficiaries across a fragmented archipelago. While existing studies have examined the program’s budgetary design and nutritional outcomes, comparatively little research has explored how logistics unfolds from the perspective of the people who operate it. This study employed a descriptive qualitative case study design focused on a Regional Implementing Unit in West Java, drawing on in-depth interviews with program coordinators, kitchen managers, couriers, and school-level beneficiary representatives, complemented by field observation and document review. Data were analyzed thematically following an established qualitative coding approach. Four interrelated themes emerged: fragmentation of last-mile distribution, vulnerability of the micro-cold chain, inaccuracy in demand signals, and variability among local suppliers. These themes converge on a shared condition, namely the absence of coordination and monitoring mechanisms linking kitchens, couriers, and beneficiaries. The findings suggest that simple, locally grounded route-planning and cold chain monitoring practices offer a more sustainable path toward efficiency than cost-cutting measures alone. As a single-site qualitative study, the findings are context-bound and point to the need for comparative research across Indonesia’s diverse regional settings.